Tommaso Giustiniani, wealthy of books - Piero Scapecchi (JLIS.it, 2021)
The article seeks to examine the book collection which Tommaso Giustiniani (1477-1528) brought with him in Holy Hermitage (Eremo) of Camaldoli from Venice when the Venetian nobleman became a Camaldolese monk in 1510 with the name of Paolo. The research of the volumes (27 incunabula and 12 16th century editions) with his ownership note “Thomae Iustiniani et amicorum”, gathered before his religious vocation, demonstrates the development and new attitudes of his personal interests. His studying interests modified between the period as a student at the University of Padua and his following staying in Venice, illustrating the raise of his religious reflection before his entry in Camaldoli.